2018
DOI: 10.1002/uog.18928
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of chromosomal microarray analysis in fetuses with isolated increased nuchal translucency: a French multicenter study

Abstract: Our study demonstrates the benefit of CMA in the etiological diagnosis of fetuses with isolated increased NT. It is worth noting that most (69%) of the detected pathogenic CNVs were cryptic. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 35 publications
6
49
4
1
Order By: Relevance
“…This rate is higher than that observed by Lichtenbelt et al . (11%) or in the French multicenter study (12%); while the respective rate varies in large series including high‐risk fetuses, from 11% in the study of Khalil et al ,. to 21% in a study from the FMF.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…This rate is higher than that observed by Lichtenbelt et al . (11%) or in the French multicenter study (12%); while the respective rate varies in large series including high‐risk fetuses, from 11% in the study of Khalil et al ,. to 21% in a study from the FMF.…”
Section: Discussioncontrasting
confidence: 61%
“…A strength of this study is that genetic testing was performed consistently during the study, using a protocol for increased NT that was set up in our center in 2002 and was updated in 2013 to replace karyotyping with CMA. In addition, the incidence of common trisomies in this study (30%) was higher than that described previously, probably due to the advanced maternal age of this population, thus minimizing the reported proportion of atypical anomalies that were missed by cfDNA testing.…”
Section: Discussioncontrasting
confidence: 59%
“…Lund et al reported one of the highest diagnostic rates (28.8%, 38/132) of chromosomal aneuploidies and the highest detection rate (12.8%, 12/94) of pathogenic CNVs detected by CMA in fetuses with an NT ≥3.5 mm [17]. A French multicenter retrospective study reported one of the largest populations of increased NT and found that 16 (2.7%) pathogenic CNVs could be detected by CMA [16]. Pan et al in China found that 5.7% of pathogenic CNVs could be detected by CMA [21].…”
Section: Discussionmentioning
confidence: 99%
“…Especially in cases with structural anomalies found during prenatal imaging examinations, CMA can detect another 5.6% pathogenic copy number variants (CNVs) in isolated defects and 9.1% pathogenic CNVs in multiple defects [14]. Recent studies have concluded different detection rates for pathogenic CNVs in cases with increased NT (0-15%) [15][16][17]. Some microdeletion/microduplication syndromes, including 22q11.2 deletion syndrome, have been found to be associated with enlarged NT thickness [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…An increased NT (≥3.5 mm, or >99th percentile) is correlated not only with chromosomal aneuploidies, but also with important defects of the heart and arteries, skeletal dysplasia to a considerable extent, as well as some genetic syndromes. In addition, when these defects occur, there is an increased risk of miscarriage, intrauterine fetal death, or delayed development [1,2].…”
Section: Introductionmentioning
confidence: 99%